A decentralized consensus application using blockchain ecosystem - Chetana Pujari; Balachandra Muniyal; Chandrakala C. B. (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The consensus is a critical operation of any decision-making process. It involves a set of eligible members; whose decision need to be honored by taking their acknowledgment before making any decision. The traditional consensus process follows centralized architecture, the members need to rely on and trust this architecture. The proposed system aims to develop a secure decentralized consensus application in the untrusted environment by making use of blockchain technology along with smart contract and interplanetary file system (IPFS).